Effect of Radiation On Dosimetric and Optical Properties of Dyed Pva/Ch and Dyed Pvb/Ch Blends - Baha, Azlina (2005)
Crystal violet doped polyvinyl alcohol blended with chloral hydrate (CV doped PVNCH) and methyl green doped polyvinyl butyral blended with chloral hydrate (MeG doped PVBICH) films were prepared by solvent casting method. The blends were irradiated with y radiation at doses of up to 110 kGy. The dosimetric and optical characteristics of the irradiated and unirradiated polymer blends were studied using UVVis- NIR and Raman Spectrometer. The CV doped PVNCH blends change colour from violet to blue at high dose (40 to 60 kGy) before bleaching at higher doses due to the formation of acid by radiation induced dechlorination of CH. The absorption spectra was measured and analysis spectrometrically. The absorbance at the absorption band at 590 nm, the characteristic of violet colour, decreases with increasing dose. The dose sensitivity Do increases where the values were 54.6, 81.9,84.0 and 117.6 kGy for CH concentration at 2.0, 3.0,4.0 and 5.0 g CH respectively. On the other hand, the absorbance at the absorption band at 620 nrn, the characteristic of blue colour, also decreases with increasing dose. The dose sensitivity Do increases where the values were 81.9, 94.3, 100.0 and 109.1 kGy for CH concentration at 2.0, 3.0, 4.0 and 5.0 g CH respectively. The consumption of CH has been studied using Raman spectroscopy by observing the reduction of C-Cl bond peak intensity at 780 cm-'. The Raman intensity decreases with increasing absorbed dose, which produces the dose sensitivity Do where the values were 35.3, 52.6,98.0 and 114.9 kGy for CH concentration at 2.0,3.0,4.0 and 5.0 g CH respectively. The influence of y rays on CV doped PVNCH and MeG doped PVBICH blend films leads to bond scission and structural orderldisorder changes, which reflected in the electronic transitions in the film and can be described by the empirical Urbach rule. The absorption edge, EOpfto r CV doped PVNCH decreases strongly with the increase of absorbed dose. However, it decreases slightly with the increase of CH concentration. The overall values decrease from 3.74 eV to 3.22 eV for doses up to 110 kGy and CH concentration from 2 g to 5 g. The optical activation energy, AE increases from 0.282 to 0.524 eV with the increase of CH concentration from 2 g to 5 g CH respectively at zero dose. The value does not change significantly with the change of dose from 20 kGy to 80 kGy and CH concentration from 2 g to 5 g CH. The values obtained are from 0.62 to 0.71 eV. At dose 100 kGy, AE is higher from 0.834 eV to 0.908 eV for CH concentration at 2 g to 5 g CH, except at 3 g the value was found to be 1.025 eV. The optical energy band gap, E, value for CV doped PVAICH blend films decreases with increasing dose and CH concentration for direct and indirect allowed transitions The values of the direct optical energy band gap, E, are from 3.64 eV to 4.00 eV, while for indirect optical band gap are from 2.84 eV to 3.60 eV. The MeG doped PVBICH blends show no colour change but starts to bleach at lower yray doses of 25 kGy. The absorbance at the absorption band at 425 nm, the characteristic of yellow colour, decreases with increasing dose. The dose sensitivity Do increases where the values were 13.5, 16.7, 18.7 and 23.0 kGy for CH concentration at 2.0, 3.0, 4.0 and 5.0 g CH respectively. On the other hand, the absorbance at the absorption band at 650 nrn, the characteristic of green colour, also decreases with increasing dose. The dose sensitivity Do increases where the values were 14.5, 16.4, 19.5 and 20.9 kGy for CH concentration at 2.0, 3.0, 4.0 and 5.0 g CH respectively. Analysis from Rarnan spectra show that the intensity of C-Cl bond at 780 cm" decreases with increasing absorbed dose. The dose sensitivity Do increases where the values were 8.2, 9.5, 15.5 and 20.5 kGy for CH concentration at 2.0,3.0,4.0 and 5.0 g CH respectively. The absorption edge, EOpt for MeG doped PVBICH decreases strongly with the increase of absorbed dose. Nevertheless, it decreases slightly with the increase of CH concentration. The overall values decrease from 3.68 eV to 3.25 eV for doses up to 25 kGy and CH concentration from 2 g to 5 g CH. The optical activation energy, AE increases with increasing of doses and CH concentration. The value does not change significantly at zero dose where the value obtained from 0.10 10 to 0.1404 eV for 2 g to 5g CH respectively. The overall values increase from 0.10 10 eV to 0.7355 eV for doses up to 25 kGy and CH concentration from 2 g to 5 g CH. The optical energy band gap, E, value for MeG doped PVBICH blend films decreases with increasing dose and CH concentration for direct and indirect allowed transitions The values of the direct optical energy band gap, E, are from 3.79 eV to 3.57 eV, while for indirect optical band gap are from 3.62 eV to 2.90 eV. In conclusion, was shown radiation effects by y-rays on CV doped PVAICH and MeG doped PVB/CH blend films, which affected the dosimetric and optical properties, could be evaluated with suitable reproducibility by measuring the optically stimulated.